Inovasi Pendidikan: : Kunci dalam Meningkatkan Profesionalisme Pendidik di Era Digital - Rizkya Rudianti, Sandra; Dwi Yanti, Syarifah; Rustini, Tin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
In the rapidly developing digital era, innovation in education is the key to increasing the professionalism of educators. Educators are faced with the challenge of continuing to develop their skills to meet the demands of the times and the increasingly dynamic needs of students. Therefore, innovation in teaching methods, the use of technology in learning, and the development of relevant and adaptive curricula are very important. Three main aspects of innovation strategies need to be considered in increasing the professionalism of educators, namely: a) self-development strategies, b) scientific publication strategies, and c) innovative work strategies. This research uses the literature review method, identifying and highlighting relevant themes, and documenting important results, frameworks, and instruments from previous research that can serve as a basis for further work. This research aims to evaluate educational innovations in Indonesia to increase the professionalism of educators in the digital era. The research results show that many benefits can be obtained from educational innovation for the professionalism of educators and that several strategies are needed to improve educational innovation, such as self-development as an educator, scientific publications, and innovative work that trains the abilities of educators so that they can further develop in the future.